Changes in the etiology of viral lower respiratory tract infections in hospitalized children in Wenzhou, China: 2008‐2017. Issue 8 (17th January 2020) - Wen, Shunhang; Yu, Mengfei; Zheng, Guifeng; Lv, Fangfang; Chen, Xiaofang; Lin, Li; Li, Changchong; Zhang, Hailin
Abstract: This study investigated the seasonality and secular trends in the etiology of viral lower respiratory tract infections (LRTIs) among hospitalized children in Wenzhou, southeastern China. A retrospective review was conducted concerning viral LRTIs in children hospitalized at a university hospital between January 1, 2008 and December 31, 2017. Direct immunofluorescence was used to detect respiratory syncytial virus (RSV), adenovirus (AdV), influenza A virus (Inf A), influenza B virus (Inf B), and human parainfluenza virus types 1 to 3 (hPIV1‐3). Of 89 898 children tested, at least one viral respiratory pathogen was identified in 25.6% and multiple pathogens were identified in 0.4%. RSV (17.6%), hPIV3 (4.0%), and AdV (2.2%) were the most frequently detected pathogens. The proportion of positive samples varied with age and was the highest in children aged <6 months (36.2%). Seasonal differences were observed in RSV, AdV, Inf A, Inf B, hPIV1, and hPIV3 infections. There was a declining trend in the proportion of positive samples over time, primarily due to a decrease in RSV and hPIV3 infections. RSV, hPIV3, and AdV were the most common viral respiratory pathogens identified among hospitalized children with LRTIs. The distribution of viruses varied with age and season. Highlights: Respiratory tract infections in children.